Traffic speed management - Subotić Jovana Lj.; Jovičić Olivera S.; Simić Marija D.; Mitrović Đurđija V. (Tehnika, 2014)
Speed, and vehicles themselves, affect the level of service and road safety, quality of life, noise from traffic, the environment, health, air pollution, emission of carbon dioxide, global warming, the economy and consumption of non-renewable energy such as oil. Therefore, the speed management of the traffic of multiple significance and that should be primarily to provide effective and economical conditions of the modern and preventive protection of human life as the greatest treasure and then the material resources. The way to accomplish this is by using various (different) measures such as: appropriate planning and projecting roads and streets, speed control, the legislation, enforcement, campaigns, education, advanced technologies (ITS).